Chinese forearm flap technique in thumb injury: a case report - ., Zainarda; Yuda Asmara, A. A. Gde; Caksana, Putu Suehandika (International Journal of Research in Medical Sciences, 2018)
Hand injuries which involve substantial skin loss require immediate soft tissue cover to achieve early wound closure and to minimize wound infection and scarring. In 1978, Dr. Yang Guofan and Dr. Chen Baoqui described a flap from the forearm based on the radial artery or Chinese Forearm Flap. A 30-year-old male was admitted to the emergency room because of crush injury. From physical examination we found crush injuries of left hand followed with open wound between 1st and 2nd finger at dorsal and palmar side with muscle, tendon, and bone exposed, with open dislocation left 1st carpometacarpal joint, open fracture dislocation left 1st metacarpophalank joint, open fracture Left Base 2nd, 4th metacarpal, open dislocation 3rd base metacarpal, open fracture left trapezoid, open left trapezium. Soft tissue injuries of the hand which require flap cover pose a problem mainly because of the apparent lack of availability of local tissue. Wound healing problems can result in an impaired functional outcome. For complication, initially, sensory disturbances can be found in 17-75% but decrease during the next months. This radial forearm flap method of post-traumatic thumb reconstruction nowadays doesn’t require expert microsurgical knowledge, which is indispensable in case of replantation or revascularization of the amputated thumb. Correct planning and elevation presupposed the flap success rates average at least 90% with no relevant limitations in strength, motion and hemodynamics in the forearm or hand and non-disturbing sensory and cosmetic outcome at the donor site.